Dynamic cerebral autoregulation in anterior and posterior cerebral circulation during cold pressor test - Washio, Takuro (J Physiol Sci, 2020)
We hypothesized that cerebral blood flow (CBF) regulation in the posterior circulation differs from that of the anterior circulation during a cold pressor test (CPT) and is accompanied by elevations in arterial blood pressure (ABP) and sympathetic nervous activity (SNA). To test this, dynamic cerebral autoregulation (dCA) in the middle and posterior cerebral arteries (MCA and PCA) were measured at three different conditions: control, early phase of the CPT, and the late phase of the CPT. The dCA was examined using a thigh cuff occlusion and release technique. The MCA and PCA blood velocities were unchanged at CPT compared with the control conditions despite an elevation in the ABP. The dCA in both the MCA and PCA remained unaltered at CPT. These findings suggest that CPT-induced elevations in the ABP and SNA did not cause changes in the CBF regulation in the posterior circulation compared with the anterior circulation.